2008
DOI: 10.1088/0264-9381/25/19/195012
|View full text |Cite
|
Sign up to set email alerts
|

Horizons in Robinson–Trautman spacetimes

Abstract: The past quasi-local horizons in vacuum Robinson-Trautman space-times are described. The case of a null (non-expanding) horizon is discussed. It is shown that the only Robinson-Trautman spacetime admitting such a horizon with sections diffeomorphic to S 2 is the Schwarzschild space-time. Weakening this condition leads to the horizons of the C-metric. Properties of the hypersurface r = 2m are examined.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 11 publications
5
19
0
Order By: Relevance
“…In the context of vacuum Robinson-Trautman spacetimes with Λ = 0, past (white-hole) horizons were already studied [11,14,15,16,17]. Following the approach outlined by Penrose [33,34], Tod in [11] explicitly derived the equation for an outer boundary of marginally past-trapped 2-surfaces at any constant retarded time u, and subsequently proved the existence and uniqueness of its smooth solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of vacuum Robinson-Trautman spacetimes with Λ = 0, past (white-hole) horizons were already studied [11,14,15,16,17]. Following the approach outlined by Penrose [33,34], Tod in [11] explicitly derived the equation for an outer boundary of marginally past-trapped 2-surfaces at any constant retarded time u, and subsequently proved the existence and uniqueness of its smooth solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they performed numerical simulations of its evolution (see also [16]). Recently, Natorf and Tafel [17] also investigated the past quasi-local horizons in vacuum Robinson-Trautman spacetimes. They showed that the marginally trapped 2-surfaces cross the surface r = 2m, and that the only spacetime which admits null nonexpanding horizon with sections diffeomorphic to S 2 is the Schwarzschild spacetime.…”
Section: Introductionmentioning
confidence: 99%
“…It is also shear-free due to the Raychaudhuri equation. Independly of topological assumptions on intersections of H with u=const we obtain the following result (see [13] for a proof)…”
Section: J Tafelmentioning
confidence: 75%
“…Global structure, trapped surfaces and asymptotic behaviour of RT spacetimes were successfully studied by Penrose [2], Foster and Newman [3], Lukacs, Perjes, Porter and Sebestyen [4], Schmidt [5], Rendall [6], Tod [7], Singleton [8], Chruściel [9,10], Chruściel and Singleton [11], Chow and Lun [12] and others. In this communication we summarize our results [13] on trapped surfaces and quasi-local horizons in RT spacetimes. These geometrical objects play an important role in modern theory of black (or white) holes (see e.g.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation